Insights into the storage stability of ammonia in polyester aluminum bags - Vikrant K.; Roy K.; Kim K.-H.; Bhattacharya S.S. (My University, 2025)
A list of gaseous odorants such as ammonia (and hydrogen sulfide) are generally collected using rigid containers or flexible bags for quantitative analysis. The aim of this investigation was to assess the stability of polyester aluminum bags used for gaseous ammonia sampling and storage. To this end, ammonia standards were prepared at two concentration levels of low (7.8 ppm) and high concentrations (39 ppm) and stored in the polyester ammonia bags for durations of 0, 1, 2, 4, and 6 days. These samples were then analyzed at each interval by an impinger-based indophenol method utilizing a spectrophotometer. At each pre-set period, three different mass loadings of ammonia samples were collected from the storage bag to obtain response factors (RF) for comparison between different elapsed times set for the storage. Subsequently, the relative recovery values for each interval were computed by dividing the RF for each sampling day by that of the 0th day. The relative recovery values for low and high concentration standards decreased with increasing storage time as 82.9% (day 1) to 36% (day 6) and 89.9% (day 1) to 59.7% (day 6), respectively. As such, the potentially superior recovery of ammonia from polyester aluminum bags was demonstrated (e.g., relative to other storage options introduced previously) to support its practical merit as storage media. © 2019